The Relationship Between Healthy Eating and Early Childhood Growth and Development - Nurul Al Fadhillah; Sibawaihi; Sigit Prasetyo; Nurjannah (Universitas Muhammadiyah Palu, 2025)
This study aims to determine the relationship between healthy eating patterns and the growth and development of early childhood. A healthy diet is a crucial factor in supporting physical growth and cognitive, motor, and social development in early childhood. The research method used is a literature review by analyzing books, journals, and other relevant references. Data were analyzed by relating the findings to child development theories and balanced nutrition principles. The results show that balanced intake of macro and micronutrients significantly affects height and weight growth, brain development, and children's immune systems. Implementing a healthy diet from an early age can prevent growth disorders such as stunting and improve children's quality of life.